El papel de la observación en la formalización de conceptos a partir de la contribución de la astronomía. Caso particular: nuestra estrella el sol - Arias, Marlón; Huerfano, Andrea (Revista Científica, 2011)
﻿This paper presents a pedagogical strategy for the development of observation as a research method in elementary school students in order to promote understanding of physical phenomena, based on the exploration of the basic characteristics of the sun, its main objective potentiate the basic devices of learning in basic elementary students from the development of activities to promote in a proper development of children inside and outside of the school environment. It looks for to build in recognition and constant observation of ideas around the sun that students have built in students to relation to and introduce to enable a dialogue between teacher-student destabilizing and student-studenton sun-related phenomena such as: the shadows, the existence of day and night, the appearance and composition of the sun, among others. At the same time, facilitate the incorporation of materials used for basic physics science, along with art activities that support the development of spatial and logic reasoning, seeking to encourage students to knowledge of astronomy and elements to achieve them to answer phenomena’s that happens around and find answers to event that occur in their diary activities.